Meningkatkan Hasil Belajar Matematika Siswa Pada Materi Matriks Melalui Penerapan Model Pembelajaran Kooperatif Tipe NHT - Arham, Arham; Zakaria, Perry; Katili, Nancy; Damayanti, Taulia (Jambura Journal of Mathematics Education, 2023)
The purpose of this study was to improve students' mathematics learning outcomes on matrix material through the application of cooperative learning model type Numbered Head Together (NHT). The subjects of this study were 23 students of class XI IPA-2 SMA Negeri 7 Prasetya Gorontalo in the academic year 2022/2023. Data collection techniques consisted of observation and tests. The research instrument is in the form of teacher and student activity observation sheets and tests in the form of description questions. This research is a Classroom Action Research using the Kemmis and Mc Taggart model with planning, action implementation, observation, and reflection stages. Data analysis techniques in this study consisted of data analysis of observation results and analysis of learning outcomes tests. The results showed that in cycle 1, the average observation of teacher activities that obtained at least good criteria was 81.25%, the average observation of student activities that obtained at least active criteria was 71.43%, the percentage of completeness of students' math learning outcomes was 60.87%. Because cycle 1 has not yet reached the action success indicator, the research continued to cycle 2. In cycle 2, the percentage of teacher activity observation results that obtained at least good criteria was 100%, the percentage of student activity observation results that obtained at least active criteria was 92.86%, and the percentage of completeness of students' mathematics learning outcomes was 91.30%. From the results of cycle 2, it is concluded that the application of cooperative learning model type NHT can improve students' mathematics learning outcomes on matrix material.